2017
DOI: 10.1051/bioconf/20170902007
|View full text |Cite
|
Sign up to set email alerts
|

Content of metals and organic acids from experimental sparkling white wine

Abstract: This work is focused on the study of the influence of different strains of yeasts on the concentration of organic acids, metallic content, and other physical-chemical parameters from experimental sparkling white wines produced by traditional method (bottle fermented). This study was required due to climatic conditions varying from year to year, generating grape harvests with very high alcoholic potential, and very low values for total acidity. In this case, a Muscat Ottonel grape must was used and passed by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…There was no significant difference observed among the sparkling wines in terms of main organic acids as well as pH values. The most abundant acid was tartaric with an average concentration between 2.06 and 2.35 g L −1 , values similar to ones published by Focea et al, Caliari et al and Gallardo-Chacón et al [ 20 , 21 , 22 ], but much higher compared to results published by Sartor et al [ 23 ]. Conversely, malic acid concentrations were relatively low when compared to literature data by Caliari et al and Sartor and al.…”
Section: Resultssupporting
confidence: 86%
“…There was no significant difference observed among the sparkling wines in terms of main organic acids as well as pH values. The most abundant acid was tartaric with an average concentration between 2.06 and 2.35 g L −1 , values similar to ones published by Focea et al, Caliari et al and Gallardo-Chacón et al [ 20 , 21 , 22 ], but much higher compared to results published by Sartor et al [ 23 ]. Conversely, malic acid concentrations were relatively low when compared to literature data by Caliari et al and Sartor and al.…”
Section: Resultssupporting
confidence: 86%
“…This can be attributed to their concentrations of proteins, carbohydrates, and phenolic compounds, which contain carboxyl, hydroxyl, sulphate, phosphate, and amino groups capable of binding metal ions [ 102 ]. Existing research papers generally report low amounts of heavy metals in wine [ 58 , 103 , 104 ]. According to Orescanin et al [ 58 ], red wine usually contains higher concentrations of metal elements than white wine.…”
Section: The Presence Of Heavy Metals In Foodmentioning
confidence: 99%
“…Some processes (ion exchange, reverse osmosis, and adsorption) contribute to a significant reduction of metals [ 2 ]. Focea et al [ 103 ] reported an increase in heavy metals during the storage of sparkling wines, which was influenced by the evolution of pH, the activation of prosthetic metalloenzymes, and the ionic balance. Andrieș et al [ 104 ] reported a major difference in metal profile when reverse osmosis was applied to obtain low-alcoholic white wines.…”
Section: The Presence Of Heavy Metals In Foodmentioning
confidence: 99%